The mosses of Mount Tambuyukon, Kinabalu Park, Malaysian Borneo - Monica Suleiman; Rimi Repin; Nurul Jannah Rajian; Yong, Kien-Thai (Penerbit UMS, 2022)
A total of 103 species, two subspecies and two varieties of mosses in 55 genera and 26 families were collected from Mount Tambuyukon in August 2008. This represents ca. 16.3% of the mosses reported from Sabah and ca. 13.9% of the mosses reported for Borneo. Amongst the 107 taxa, three species of mosses are new for Sabah, namely Acroporium aciphyllum Dixon, Garovaglia baeuerlenii (Geh.) Paris and Macromitrium angustifolium Dozy & Molk. The largest moss family collected here is Sematophyllaceae (13 taxa) followed by Leucobryaceae (11 taxa), and both Dicranaceae and Orthotrichaceae (10 taxa). In conclusion, Mount Tambuyukon sustains a rich and interesting moss flora, including several rare and endemic species.